Sustainability of Hospital Accreditation Programs in Low and Middle-Income Countries: Lessons learned from Sri Lanka - Dilantha Dharmagunawardene; Mark Avery; Paula Bowman; David Greenfield; Reece Hinchcliff (ACHSM, 2024)
Objective: Many hospital accreditation programs developed for or implemented in Low and Middle-Income Countries (LMICs), including Sri Lanka, have been discontinued due to multiple factors. This study was conducted to elicit and analyse factors influencing the Sri Lankan hospital accreditation program that was initiated in 2015. Design: This case study employed document reviews and 18 key informant interviews with stakeholders involved in Sri Lanka's accreditation program. Collected data were thematically analysed. Setting: Sri Lankan healthcare system. Main outcome measures: Data extraction was guided by the constructs of the ACES-GLEAM Framework, which was developed based on the results of a scoping review. Results: Barriers identified were frequent changes in the leadership and strategic plans, lack of awareness and competencies on accreditation among local stakeholders, and non-alignment of accreditation standards with the local health system context hampered by resource and infrastructure constraints. Enablers for program development commonly raised were the commitment of stakeholders, the availability of institutional structures for quality assurance, donor funding from the World Bank, and technical expertise and surveyor training by the Australian Council on Healthcare Standards International. Conclusions: The study identified that multiple factors contributed to the poor sustainability of the Sri Lankan accreditation program. These findings can be useful reflections and guidelines for the accreditation stakeholders to establish sustainable and effective programs in LMICs.